PENINGKATAN KEMAMPUAN GURU DALAM MENGANALISATES BUTIR SOAL SECARA KOMPUTERASI DI SMA MUHAMMADIYAH BANGKINANG - Defrizal Hamka; Berry Kurnia Vilmala; Gustia Angraiani (Jurnal Pengabdian UntukMu NegeRI, 2018)
Assessment of the learning process and assessment of learning outcomes are two very important things in education. Assessment of processes and results is a part that blends with the learning process activities. Assessment of learning processes and results is used as a reference to improve the overall learning process. One part of the assessment of learning outcomes is a test. Schools still use multiple choice tests as a measure to determine the success of students. However, schools in this case the teachers have not been able to determine the quality and feasibility of the questions that are used well. Moreover, not many teachers understand how to analyze items in a computerized manner. Supposedly, before a double question is used as a measure of a learning process, the thing to do is analyze the problem. So that it can be determined questions that have good quality, questions that must be corrected, and which questions should be discarded. The training activity analyzed the items with computerization for the teachers at Muhammadiyah Bangkinang Senior High School to run well and smoothly. This training provides knowledge and understanding of the importance of conducting item analysis at this time. Thus this activity is important, because the school in this case the teacher gets the knowledge and skills in analyzing question items through computarization, namely using the software Quest. So that in the future teachers will easily make improvements to the problems at school.